Pengaruh Promosi Online dan Persepsi Harga Terhadap Keputusan Pembelian (Studi Kasus Pada Nithalian Collection Bima) - Rosida Rosida; Intisari Haryanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The purpose of this study is to determine and analyze the effect of online promotions and price perceptions on purchasing decisions (Case Study on the Nithalian Collection Bima) both partially and simultaneously. The type of research used is associative. The population used is all Nithalian Collection Bima customers. The sampling technique used was purposive sampling because the number of unknown population was known (Unknown Population) then obtained a sample of 96 respondents using the cochran formula. The research instrument uses a questionnaire with a Likert scale measurement. Data collection techniques by observation, questionnaire, interview and literature study. Data analysis methods used are validity test, reliability test, multiple regression, multiple correlation, classic assumption test, t test (partial) and F test (simultaneous). The results of this study conclude that online promotion has a significant influence on partial purchasing decisions as evidenced by the t test value of 6,371 and Sig 0,000. While price perception has a significant influence on purchasing decisions partially with a t test value of 4.348 and Sig 0.000. Furthermore, online promotions and price perceptions have a significant influence on purchasing decisions simultaneously with an F test value of 252.405 and Sig 0.000.